(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2021)
The importance of the research lies in preparing educational units with a strategy of cognitive conflict, and knowing the effect of educational units in the strategy of cognitive conflict in the performance of some offensive positions for the players of the Specialized School of Football in Kerbala. As for the research problem, it was that the researchers noticed the difficulty of the development of players in completing the correct offensive structure, due to the diversity of offensive positions, which makes the player unaware of the appropriate performance, with a weakness in the mental aspects of the player and his inability to assemble an intellectual picture of the performance of the offensive duty optimally, and for the purpose of using everything that would improve learning outcomes and achieve the desired benefit, moving from what he previously learned to what he is currently learning by using a modern knowledge strategy in the mathematical field that invests the learners’ abilities to the maximum extent possible, therefore, the researchers decided to use this strategy and try to know its effect on the performance of some offensive situations for football players. As for the objectives of the research, it was to identify the impact of the cognitive conflict strategy on the performance of some offensive positions for the players of the specialized school of football at ages (14-16) years, as well as to identify the preference for the effect between the strategy of cognitive conflict and the method used in the performance of some offensive positions in football at ages (14-16) years in the post tests.